The long-term negative impact of childhood stroke on language - Heimgärtner, Magdalena; Gschaidmeier, Alisa; Schnaufer, Lukas; Staudt, Martin; Wilke, Marko; Lidzba, Karen (Frontiers in Pediatrics, 2024)
To investigate the long-term language outcome in children with unilateral childhood strokes in comparison to children with perinatal strokes and to typically-developing individuals, and the influence of lesion-specific modifiers. Methods: We examined 9 patients with childhood strokes, acquired between 0;2 and 16;1 years (CHILD; 3 female, md = 13.5 years, 6 left-sided), 23 patients with perinatal strokes (PERI; 11 female, md = 12.5 years, 16 left-sided) and 33 age-matched typically developing individuals (CONTROL; 15 female, md = 12.33 years). Language outcome was assessed with ageappropriate tasks of the Potsdam Illinois Test of Psycholinguistic Abilities (P-ITPA) or the Peabody Picture Vocabulary Test (PPVT). For group comparisons, study specific language zscores were calculated. Nonverbal intelligence was assessed with the Test of Nonverbal Intelligence (TONI-4), language lateralization with functional MRI, and lesion size with MRIbased volumetry. Results: All 4 childhood stroke patients who had initially presented with aphasic symptoms recovered from aphasia. Patients with childhood strokes showed significantly lower language scores than the control group, but scored similar to patients with perinatal strokes, after correcting for general intelligence (ANCOVA, language z-score CHILD = -0.30, PERI = -0.38, CONTROL = 0.42). In childhood stroke patients, none of the possibly modifying factors, including lesion side, correlated significantly with language outcome. Conclusion: Childhood stroke, regardless of the affected hemisphere, can lead to chronic language deficits, even though affected children show a "full recovery". The rehabilitation of children and adolescents with childhood strokes should address language abilities, even after the usually quick resolution of clear aphasic symptoms.